Dynamic model validation using blast vibration monitoring in mine backfill. (July 2018) - Emad, Muhammad Zaka; Mitri, Hani; Kelly, Cecile
Abstract: Sublevel stoping mining methods with delayed backfill are employed for mining steeply dipping ore deposits at deeper horizons. Cemented rockfill (CRF) is used as a backfilling material for open stopes formed during mining. In primary-secondary mining sequence, blast vibrations are induced in CRF during the extraction of adjacent stopes. Higher magnitude of blast vibrations may destabilize CRF causing failure and dilution of precious ore. This paper presents a methodology for calibrating a FLAC3D numerical model, encompassing mine backfill with blast-induced vibration data recorded from field instrumentation. Two FLAC3D models are prepared, one for simulating the blasting process and the other is prepared for backfill stability analysis. The first model resulted in load vectors to be applied to backfill and rock interface. The second model showed that the backfill fails under the blast vibrations induced by the adjacent production stope. The results of the back analysis of fill failure are presented and discussed. The methodology may serve as numerical model calibration procedure for mine backfill.